Compression stocking prevents increased venous retrograde flow time in the lower limbs of pregnant women - Junior, Orlando Adas Saliba [UNESP]; Rollo, Hamilton Almeida [UNESP]; Saliba, Orlando [UNESP]; Sobreira, Marcone Lima [UNESP] (SAGE Publications, 2020)
Objectives: To analyze the effect of graduated compression stockings on the venous reflux in the lower limbs of pregnant women. Method: A controlled randomized clinical trial was performed with sixty women: intervention group (n = 30), who used compression stockings, and control group (n = 30). Using duplex-ultrasound, the reflux time and peak reflux velocity in the great saphenous vein and small saphenous vein were analyzed. Results: Great saphenous vein reflux times in the intervention group were 0.13 s at the beginning (initial) and 0.04 s at the end of pregnancy (final) in the right leg and 0.02 s and 0.34 s (p < 0.0001) in the control group. No patient in the intervention group experienced pathological reflux at the end of the pregnancy. There was a significant difference in the reflux time measured from both the great saphenous vein and small saphenous vein and peak reflux velocity between the groups. Conclusion: Compression stockings prevent increased venous reflux in lower limbs of pregnant women.
Keywords: compression stocking; controlled clinical trial; pregnancy; Varicose veins; venous insufficiency